Loucura e gênero: uma análise da escrita autobiográfica de Maura Lopes Cançado - Leisa Ferreira Amaral Gomes (2014)
This dissertation examines the autobiographical writing of the author born in Minas Gerais State, Maura Cançado Lopes (1929-1993), whose book Hospício é Deus was first published in 1965. It is a mix of literary genres, such as journal, memories and autobiography, written between 1959 and 1960, when she was at the Hospital Gustavo Riedel of the National Psychiatric Center, located at Engenho de Dentro, Rio de Janeiro - RJ. This research was developed within the field of critical social psychology and it uses as theoretical-methodological reference the method of discourse analysis, inspired by the archaeological description of Michel Foucault. It investigates the discourse of madness in the autobiographical writing by Maura Lopes Cançado, combining text and social context, marked by important gender issues. For this discussion, we adopt mainly the theoretical frameworks of Joan Scott and Judith Butler, among other authors from gender studies and, regarding the theme of madness, authors from the field of the Brazilian psychiatric reform and Michel Foucault. The book Hospício é Deus preceded the Brazilian psychiatric reform. Maura Lopes Cançado often deals with identity issues related to the condition of "being crazy." She describes other women patients and the relationships with doctors, nurses and staff, treatments and also maltreatment in the psychiatric hospital. Madness challenges the comprehension of the author and her romanticized view of the hospice as a place out of the world does not find resonance in an oppressive institutional routine.